2005
DOI: 10.1007/s10956-005-1853-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EGF and bFGF on Irradiated Parotid Glands

Abstract: Radiotherapy is common treatment for head-and-neck cancer, during which the salivary glands are often included within the radiation field. The most common side effect of this treatment is the development of oral dryness (xerostomia). This study considers the administration of epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF or FGF2) at physiological concentrations before and after irradiation in order to repair radiation-induced damage in salivary gland cells. As a preliminary examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
1
23
0
3
Order By: Relevance
“…With bFGF treatment, saliva flow rate recovered to near normal within 8 weeks after irradiation; this result is comparable to other studies that utilized adenoviral‐mediated salivary gland gene transfer 10. bFGF is a well‐known mitogen that accelerates tissue regeneration through its ability to induce angiogenesis, granulation tissue formation, and epithelial cell proliferation 8, 9. Although it is known to have a short half‐life, which could limit the efficiency of direct injection, the efficacy indicated by our data was satisfactory.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…With bFGF treatment, saliva flow rate recovered to near normal within 8 weeks after irradiation; this result is comparable to other studies that utilized adenoviral‐mediated salivary gland gene transfer 10. bFGF is a well‐known mitogen that accelerates tissue regeneration through its ability to induce angiogenesis, granulation tissue formation, and epithelial cell proliferation 8, 9. Although it is known to have a short half‐life, which could limit the efficiency of direct injection, the efficacy indicated by our data was satisfactory.…”
Section: Discussionsupporting
confidence: 74%
“…bFGF is a well‐known mitogen that influences cell migration, differentiation, and regeneration. The effects of bFGF have been examined in atrophic salivary glands,8 irradiated parotid glands in vitro9 and through adenoviral‐mediated salivary gland gene transfer in vivo 10. Although bFGF is considered effective against irradiation damage to salivary glands, it also poses a risk in that it may promote cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in other implantable devices that have been cleared by the FDA for human use in several applications, and a significant background literature is available on expected behavior in vivo. Additionally, we, and other groups, have used this material in the water-in-oil-in-water (W/O/W) solvent extraction/evaporation, “double emulsion” manner as well as the more direct “water-in-oil” emulsion method used here to encapsulate and slowly release water soluble biologically active proteins 11 . This coating is well known to degrade by a simple hydrolysis reaction to yield the known metabolites: lactic acid and glycolic acid.…”
Section: Resultsmentioning
confidence: 99%
“…The role of apoptosis in radiation-induced damage to the salivary gland has been debated; studies in the mouse have reported significant levels of apoptotic cells (1114) while the presence of apoptosis in irradiated rats have been more variable (810). Our results indicate that a significant number of apoptotic cells could be detected in FVB mice following each fraction of radiation with little differences between the number of doses.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, induction of apoptosis is variable with reports ranging from minimal levels to significantly higher levels (810). In the mouse, significant levels of apoptosis can be detected, which increases with radiation dose (11–16).…”
Section: Introductionmentioning
confidence: 99%